Pilot Study: Influence of oral habits in the development of malocclusions in infants - Álvarez - Páucar, María Angélica (2011)
The aim of the study was to determine the influence of oral habits more prevalent in the dental occlusion of infants who attended the dental clinic of San Marcos University. This is a descriptive and cross-section study in patients attending the Infant Clinic of the Child, in the 2010. The sample consisted in 50 infants who recorded the first plane of occlusion. The data collection was obtained through a survey to parents and subsequently performed clinical examination for registration of malocclusion in children. They applied the chi-square test of Pearson r (SPSS 17) with a significance level of 95 % (p <0.05).Our study observed a relation between the common digital suction depth of the palate with 60 % (11 infants) (p 0.01). Also was no relation between the plane and finger sucking terminal for within the age range of 19-36 months, also there was a terminal plane (straight or distal) in 89% (8 infants) in the group with digital suction its 100 % (9 infants) (p 0.00). It study was found that a positive relation between deep palate and the habit of mouth breathing, found that 100% of them (p 0.00), being the age of the infants of 19-36 months, those who had the highest prevalence. The results showed that early onset most prevalent habits (finger sucking and mouth breathing 21 % 12 %) is most apparent between ages (19 - 36 months) on dental malocclusion. The thumb sucking habit has an impact on the depth of the palate and was relation of the rectum terminal plane and distal step.